BRAND LOYALTY AND SATISFACTION TOWARDS TOILET SOAPS: A STUDY OF URBAN CONSUMERS IN WARANGAL DISTRICT (A. P.) - M. S. Sarma and V. Rana Pratap (Abhigyan, 2011)
The marketing scenario in India has undergone vast change since 1991 due to the economic reforms. Post-liberalization, competition intensified in every product line and market, which forced brands to redefine their norms of existence in all industries. In the FMCG industry, especially in toilet soap sector there has been severe competition among the MNCs, national and local players. The toilet soaps can be divided into four price segments: Premium, popular, economy and carbolic soaps. At the same time, penetration level of toilet soaps in urban areas is very high, but per capita consumption levels remain low. In this scenario, it is very important for marketers to know the consumer behavior with respect to toilet soaps, which will be very useful in adopting suitable strategies. This research paper attempts to analyze the brand loyalty, satisfaction, awareness, and switching behavior of consumers regarding soaps. It also examines the factors influencing brand choices.